Lipid metabolism and Alzheimer's disease: clinical evidence, mechanistic link and therapeutic promise - Yin, Fei (The FEBS journal, 2023)
Alzheimer’s disease (AD) is an age‐associated neurodegenerative disorder with multifactorial etiology, intersecting genetic and environmental risk factors, and a lack of disease‐modifying therapeutics. While the abnormal accumulation of lipids was described in the very first report of AD neuropathology, it was not until recent decades that lipid dyshomeostasis became a focus of AD research. Clinically, lipidomic and metabolomic studies have consistently shown alterations in the levels of various lipid classes emerging in early stages of AD brains. Mechanistically, decades of discovery research have revealed multifaceted interactions between lipid metabolism and key AD pathogenic mechanisms including amyloidogenesis, bioenergetic deficit, oxidative stress, neuroinflammation, and myelin degeneration. In the present review, converging evidence defining lipid dyshomeostasis in AD is summarized, followed by discussions on mechanisms by which lipid metabolism contributes to pathogenesis and modifies disease risk. Furthermore, lipid‐targeting therapeutic strategies, and the modification of their efficacy by disease stage, ApoE status, and metabolic and vascular profiles, are reviewed. Alzheimer’s disease (AD) is a neurodegenerative disease with multifactorial etiology, intersecting risk factors, and a lack of disease‐modifying therapeutics. In this review, converging clinical evidence defining lipid dyshomeostasis in early stages of AD is summarized followed by discussions on mechanisms by which lipid metabolism contributes to pathogenesis and modifies disease risk. Furthermore, existing and potential lipid‐targeting therapeutic strategies are reviewed.